PENGGUNAAN TEOREMA PI BUCKINGHAM PADA PENYELIDIKAN LOST HEAD UNTUK PIPA MENDATAR DENGAN ALIRAN TAK KOMPRESIBEL TURBULEN - Indah Eko Cahyani; Agus Wibowo (Engineering : Jurnal Bidang Teknik, 2011)
Lost  head  can be interpreted  as a decrease  in  the pressuregradient  and is a measure  of  resistance  to  flow  through the  pipe. Barriers  to  flow  through the  pipeline  will greatly  affect  the  power needed  in  moving the  fluid  so that the  investigation of the  losthead  on  pipe  important thing to do.  Use of  Buckingham  Pitheorem  for  dimensional  analysis  will make it easier  to analyzeand  make the  move  quicker  and directed  experiments.  With theinitial data  is a function  of the  barrier  pipe diameter,  fluidviscosity,  fluid density,  pipe length, the fluid velocity  and theroughness of  the pipe.  The results indicate  a lost  connection  headper  weight of  the fluid  (w p /)  is proportional to  the piperoughness  factor  (f) is proportional to  the length of  pipe  per  pipe diameter  (L  /  d) is proportional to  the  fluid velocity  kuwadrat  pertwo times gravity (v2/2g)Keywords: Lost head, turbulent flow, the flow channel is closed